Immunofluorescent staining of rat gastric parietal cells by human antibody unrelated to pernicious anaemia - Muller, H. K. (1971)
Immunofluorescence tests on 94 human sera reacting with rat gastric parietal cells revealed that 41 (44%) of the sera contained antibody to a rat parietal cell antigen that was distinct from the pernicious anaemia autoantigen. Ten of the sera contained antibodies to both parietal cell antigens. The remaining 53 (56%) sera contained only parietal cell antibodies of the pernicious anaemia type. We recommend that mouse gastric mucosa, which does not react with the heterologous rat parietal cell antibody, replace rat gastric mucosa for immunofluorescence diagnostic tests.